Guidelines for solving Legal Problems Concerning Supporting Sport of Local Government Organizations - Laobankho, Worawut (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were 1) to study basic information, concepts, principles, and legal theories related to sports sponsorship of local governments in Thailand and abroad, 2) to analyze legal problems related to sports sponsorships of local governments, and 3) to propose solutions that are suitable for Thailand by using a documentary research method. The research results showed that Thailand still has problems with the promotion and support of sports. Whether there are legal issues related to the support of amateur sports the local government cannot fully support amateur sports, legal problems related to professional sports support that local governments cannot support professional sports clubs, or professional sports associations at all. Because the Office of the Auditor General of Thailand has ruled that it is not the power and duty of the local administrative organization because professional sports are private activities and it is the duty of the private sector that organizes sports events to seek external or private support budgets. Therefore, the researcher agrees that the Sports Authority of Thailand Act B.E. 2558 (2015) and the Professional Sports Act B.E. 2556 (2013) should be added by specifying that local government organizations can support sports and professional sports to apply to solve problems sustainably.